Akinetic crisis in dementia with Lewy bodies. Issue 10 (11th April 2016) - Bonanni, L; Di Giacomo, R; D'Amico, A; Frazzini, V; Franciotti, R; Manzoli, L; Thomas, A; Onofrj, M
Abstract : Background and purpose: Dementia with Lewy bodies (DLB) is characterised by neuroleptic hypersensitivity. It is unclear, however, whether the neuroleptic hypersensitivity implies an increased incidence of neuroleptic malignant syndrome (NMS) or of akinetic crisis (AC), which are expressions of the same possibly lethal clinical event, and whether AC in DLB can appear independently of neuroleptic treatment. In our prospective study, we assessed the incidence of AC in a cohort of DLB as compared with that in patients with Parkinson disease (PD). Methods: In total, 614 patients with PD and 236 DLB were recruited and followed during 2005–2013. AC was diagnosed as sudden akinetic state unresponsive to dopaminergic rescue drugs, dysphagia and serological alterations without recovery for 48 h or more requiring hospital admission. Exposure to neuroleptics was specifically evaluated, because of the high implicit risk in DLB. Results: 24 patients with PD (3.9%) and 16 patients with DLB (6.8%) developed AC. 77 (32.6%) DLB and 32 (5.2%) PD were exposed to typical neuroleptics, but only 8 DLB and 3 PD presented with AC. Disease duration before AC was lower in DLB than in PD group (p<0.01). Outcome was fatal in 8 patients with (50%) DLB and 3 (12.5%) PD (p=0.05). When age and use of neuroleptics were adjusted for into a Cox proportional hazards model predicting time to AC, the HR of patients with DLB was 13.0 (95% CI 4.23 to 39.9; p<0.001). Conclusions: AC in DLB can appear independently of neuroleptic treatment, occurs earlier and is more frequently fatal than in PD.